2009
DOI: 10.1590/s0102-05362009000400026
|View full text |Cite
|
Sign up to set email alerts
|

Densidades de plantio na produtividade e qualidade de frutos de melancia

Abstract: A melancia (Citrullus lanatus (Thunb.) Matsum. & Nakai) é uma Cucurbitaceae de grande expressão econômica e social, possuindo propriedades nutricionais e terapêuticas que aumentam o interesse do consumidor pelo seu fruto (Dias et al., 2006).No Brasil, a preferência do mercado consumidor leva em consideração o tamanho e formato do fruto, coloração da polpa, teor de sólidos solúveis, presença ou ausência de sementes, principalmente. Mais recentemente destaca-se o surgimento de novos tipos de melancias, as chamad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 5 publications
3
21
1
16
Order By: Relevance
“…When considering the leaf area alone, it was observed that the plants in this spacing presented a larger area to intercept the incident solar radiation. According to Silva et al (2010), the reduction of plant density increased the leaf area, however, it reflects in lower production per plant (Ramos et al, 2009), as observed in Table 5. In this sense, the plant population acts on the penetration of solar radiation and on the balance between vegetative growths (Kunz et al, 2007;Taiz and Zeiger, 2013).…”
Section: Resultsmentioning
confidence: 82%
“…When considering the leaf area alone, it was observed that the plants in this spacing presented a larger area to intercept the incident solar radiation. According to Silva et al (2010), the reduction of plant density increased the leaf area, however, it reflects in lower production per plant (Ramos et al, 2009), as observed in Table 5. In this sense, the plant population acts on the penetration of solar radiation and on the balance between vegetative growths (Kunz et al, 2007;Taiz and Zeiger, 2013).…”
Section: Resultsmentioning
confidence: 82%
“…Frutos de formato arredondado geralmente não apresentam variações consideráveis entre os valores de comprimento e diâmetro, como observado, por exemplo, nas cultivares Crimson Sweet Super e Elisa, que apresentaram diferença média de 7,15 cm entre comprimento e diâmetro, inferiores aos 16,8 cm encontrados na cultivar Juliane para as mesmas variáveis (Tabela 2). Segundo Ramos et al (2009), as características dimensionais (comprimento e diâmetro), quando avaliadas apenas em função de diferentes densidades de plantio, não sofrem variações significativas, indicando que as divergências dessas variáveis entre as cultivares ocorreram em razão das características intrínsecas de cada cultivar.…”
Section: Resultsunclassified
“…Campagnol et al (2012) studied mini watermelons as a function of pruning height and plant density and reported that the latter affected soluble solids, titratable acidity and ascorbic acid. Gualberto et al (2001) assessed the effect of spacing and number of stems in melon plants and observed differences for soluble solids, whereas Ramos et al (2009) found no differences in mini watermelon quality traits as a function of plant density.…”
Section: Palavras-chavementioning
confidence: 99%